Enhancing the Fracture Resistance and Impact Toughness of Mechanically Frothed Epoxy Foams with Hollow Elastomeric Microspheres. Issue 12 (14th December 2018) - Song, Wenzhe; Tagarielli, Vito L.; Lee, Koon‐Yang
Abstract : Front Cover : In article1800363, Koon‐Yang Lee and co‐workers present a method to enhance the fracture resistance and impact toughness of brittle epoxy foam without sacrificing its quasi‐static compressive properties using porous elastomeric microspheres. The fracture toughness and Charpy impact strength of hollow elastomeric microsphere‐filled epoxy foams improves by 15% and 33%, respectively, compared with neat epoxy foams.